Implementasi Edukasi Pemulihan Cidera Muskuloskeletal pada Petugas Kebersihan, Security dan Taman di Lingkungan RW 13 Kebraon Surabaya - Pramono, Dominggus Ruku Yudit; Djajanti, Cicilia Wahju; Wahyuni, Lusia Dwi Sri (Jurnal Abdimas Kesehatan (JAK), 2024)
Physical activity is a functional ability that is carried out by every individual every day. Apart from physical activity, every individual also has habits, namely sports activities. Sports are fun and healthy for anyone who does sports activities. Starting from an early age to the elderly, they may be encouraged to exercise regularly with the aim of maintaining fitness. Physical activities and sports are also prone to causing injury if you are not properly prepared before and after the activity or sport. Injury is a trauma to the integumentary, muscular and skeletal systems caused by physical activity. Injuries during physical activity/sports are caused by various factors, including incorrect training methods, structural abnormalities and physiological weaknesses in the function of supporting tissues and muscles.